The Impact of Islamic Work Ethics and Organizational Justice on Organizational Citizenship Behavior: The Mediating Role of Organizational Commitment - Hadi, Syamsul; Rokhman, Nur; Kirana, Kusuma Chandra; Andleeb, Naima; Purnasari, Eni (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2023)
Abstract. Organizational Citizenship Behavior is not exhibited by all employees within a company. To effectively accomplish objectives, the management must possess a comprehensive understanding of organizational justice, the significance of Islamic values, and the extent to which employee dedication is established. The research aims to analyze the effect of Islamic work ethic and organizational justice on organizational citizenship behavior mediated by organizational commitment. This article employs a quantitative method, with data obtained through questionnaires distributed to 65 respondents from an Indonesian company and analyzed using structural equation modeling. The study shows that the Islamic work ethic positively and significantly affects organizational citizenship behavior and commitment. Organizational justice positively and significantly affects organizational citizenship behavior and commitment. Meanwhile, organizational commitment has a positive and significant effect on organizational citizenship behavior and has been proven to be able to mediate such relationships.  Abstrak. Tidak semua karyawan menunjukkan perilaku organisasi kewarganegaraan. Untuk mencapai tujuannya secara efektif, manajemen harus memiliki pemahaman komprehensif tentang keadilan organisasi, pentingnya nilai-nilai Islam, dan sejauh mana dedikasi karyawan dibangun. Penelitian ini bertujuan untuk menganalisis pengaruh etos kerja Islam dan keadilan organisasi terhadap perilaku organisasi kewarganegaraan yang dimediasi oleh komitmen organisasi. Artikel ini menggunakan metode kuantitatif, dengan data diperoleh melalui kuesioner yang disebarkan kepada 65 responden di satu perusahaan di Indonesia. Sedangkan analisis datanya menggunakan model persamaan struktural. Hasil penelitian menunjukkan bahwa etos kerja Islam berpengaruh positif dan signifikan terhadap perilaku dan komitmen kewargaanorganisasi. Keadilan organisasi berpengaruh positif dan signifikan terhadap Perilaku Organisasi Kewarganegaraan dan Komitmen Organisasi. Komitmen organisasi berpengaruh positif dan signifikan terhadap Perilaku Organisasi Kewarganegaraan dan terbukti mampu memediasi hubungan tersebut.